Netflix's Problems With Net Neutrality and Gats Principles With Indonesian National Regulations - Yosuadi, Dolok (Sekolah Tinggi Ilmu Hukum Tambun Bungai Palangka Raya, 2023)
This research discusses the need for the application of strict regulations, especially for the Netflix Over The Top (OTT) service, as an Information Technology service run by telecommunication services with content in the form of data, information or multimedia that runs through the internet network, the services delivered are through the internet network. , infrastructure owned by the operator, but without any cooperation with the operator or the government in Indonesia. The presence of Netflix in Indonesia can be likened to a trader selling in a house without asking the owner for permission, because it does not respect state sovereignty by not taking care of licensing, and there is no protection for the user community. Regulations related to OTT services such as Netflix have not been explicitly regulated in existing laws in Indonesia, only in broad terms are regulated in regulations on telecommunications. The government should immediately issue regulations related to OTT services such as Netflix to ensure legal certainty and justice for parties in conducting business, especially in the telecommunications sector, according to Indonesia's international commitments and the state's commitment to protect the rights of all Indonesian citizens.